Penyelesaian Sengketa Cargo atas Keterlambatan terhadap Pengangkutan Muatan Melalui Kapal Laut (Studi Kasus Di Pt. Bali Intercont Cargo) - Mey Anjani; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2022)
The implementation of cargo transportation by ship which is the main component in business activities allows the emergence of problems on the part of consumers or users of transportation services for the losses incurred, such as the problem of delays in the transportation of cargo. The purpose of this study was to determine the implementation of cargo transportation agreements and dispute resolution at transportation service providers for delays in transporting cargo by ship. This study uses empirical legal research methods, with a statutory approach and a fact approach. Primary data is the source of data in this study. Data were analyzed using quantitative methods. The results of this study indicate that the settlement of disputes over delays in the transportation of cargo by ship at PT. Bali Intercont Cargo by using alternative dispute resolution in the form of negotiations with consumers or users of transportation services regarding rescheduling of cargo transportation.